Young Sherlock Holmes [videorecording (DVD)] - Levinson, Barry; Rowe, Nicholas, 1966-; Cox, Alan, 1970-; Ward, Sophie; Higgins, Anthony, 1947-; Fleetwood, Susan, 1944-1995; Jones, Freddie, 1927-2019-; Stock, Nigel; Ashton-Griffiths, Roger; Rhodes, Earl; Doyle, Arthur Conan, 1859-1930 (Paramount Home Entertainment, 2003)
When assorted people start having inexplicable delusions that lead to their deaths, a teenage Sherlock Holmes investigates.